Modern methods of teaching the Russian language in higher educational institutions - Chubaeva Farangiz Koldosh kizi (Genius Journals, 2022)
The development of information technologies affects the choice of methods and techniques for teaching the Russian language in institutions of secondary vocational education. The use of modern methods and techniques developed by leading philologists and teachers helps to improve the quality of students' knowledge of language tools and the motivation for their further learning. The main subject of education in institutions of secondary vocational education is a student, so all teaching aids should be aimed at developing his spiritual potential and creative abilities.The anthropocentric approach to education, the method of problem-based learning and innovative techniques, combined with the traditional paradigm, contribute to the acquisition of communicative, linguistic, linguistic and cultural competencies by students, which is the goal of teaching the Russian language in institutions of secondary vocational education
Keywords: Secondary Vocational Education; Anthropocentrism; Communicative Competence; Fishbone